Home-Based EEG Neurofeedback Intervention for the Management of Chronic Pain - Birch, Nick; Graham, Jon; Ozolins, Christine; Kumarasinghe, Kaushalya; Almesfer, Faisal (Frontiers in Pain Research, 2022)
Background Chronic pain and associated symptoms often cause significant disability and reduced quality of life (QoL). Neurofeedback (NFB) as part of a Brain Computer Interface can help some patients manage chronic pain by normalising maladaptive brain activity measured with electroencephalography (EEG). Objectives This study was designed to assess the efficacy and safety of a novel home-based NFB device for managing chronic pain by modifying specific EEG activity. Methods A prospective, single-arm, proof-of-concept study was conducted between June 2020 and March 2021 among adults with chronic pain (registered with ClinicalTrials.gov NCT04418362). Axon EEG NFB systems for home use were provided to each, and 32–48 NFB training sessions were completed by the participants over 8-weeks. The primary outcome was self-reported pain. Assessment of central sensitisation, sleep quality, affective symptoms, change in QoL, adverse events during use and EEG correlations with symptoms were secondary outcomes. Results Sixteen participants were enrolled. Eleven reported pain relief following NFB training, eight reporting clinically significant improvements. Central sensitisation symptoms improved by a third (p < 0.0001), sleep quality by almost 50% (p < 0.001), anxiety reduced by 40% (p = 0.015), and QoL improved at final follow-up for 13 participants. The majority (69%) of participants who upregulated relative alpha reported improved pain, and those who downregulated relative hi-beta reported improved pain, reduced anxiety and depression scores. There were no adverse events during the trial. Conclusions Home-based NFB training is well-tolerated and may provide relief for sufferers of chronic pain and its associated symptoms. Summary Axon, a home-based NFB training device, can positively influence pain and associated symptoms in a proportion of people with chronic pain.